2013
DOI: 10.1159/000351849
|View full text |Cite
|
Sign up to set email alerts
|

Evaluations of the Selectivities of the Diacylglycerol Kinase Inhibitors R59022 and R59949 Among Diacylglycerol Kinase Isozymes Using a New Non-Radioactive Assay Method

Abstract: Ten mammalian diacylglycerol kinase (DGK) isozymes (a-γ) have been identified. Recent studies have revealed that DGK isozymes play pivotal roles in a wide variety of pathophysiological functions. Thus, it is important to be able to easily check DGK activity in each pathophysiological event. Moreover, the conventional DGK assay is quite laborious because it requires the use of a radioisotope and thin-layer chromatography including multiple extraction steps. In order to minimize the laborious procedures, we esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
104
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 81 publications
(117 citation statements)
references
References 45 publications
12
104
0
1
Order By: Relevance
“…Therefore, if a DGK ␣ -selective inhibitor is identifi ed and developed, it would reversely attenuate cancer cell proliferation and simultaneously activate T-cell function. There are two commercially available DGK inhibitors, 6-(2-{4-[(4-fl uorophenyl)phenylmethylene]1-piperidinyl}ethyl)-7-methyl-5 H -thiazolo-(3,2-a )pyrimidin-5-one (R59022 ) ( 14,15 ) and 3-(2-{4-[bis-(4-fl uorophenyl) methylene]1-piperidinyl}ethyl)-2,3-dihydro-2-thioxo-4(1 H ) quinazolinone (R59949 ) ( 16,17 ); however, we found that R59022 and R59949 only semiselectively inhibited type I, III, and V DGKs ␣ , , and , and type I and II DGKs ␣ , ␥ , ␦ , and , respectively ( 18 ). Moreover, the IC 50 values of R59022 and R59949 were ‫ف‬ 25 M and 18 M, respectively ( 18 ).…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…Therefore, if a DGK ␣ -selective inhibitor is identifi ed and developed, it would reversely attenuate cancer cell proliferation and simultaneously activate T-cell function. There are two commercially available DGK inhibitors, 6-(2-{4-[(4-fl uorophenyl)phenylmethylene]1-piperidinyl}ethyl)-7-methyl-5 H -thiazolo-(3,2-a )pyrimidin-5-one (R59022 ) ( 14,15 ) and 3-(2-{4-[bis-(4-fl uorophenyl) methylene]1-piperidinyl}ethyl)-2,3-dihydro-2-thioxo-4(1 H ) quinazolinone (R59949 ) ( 16,17 ); however, we found that R59022 and R59949 only semiselectively inhibited type I, III, and V DGKs ␣ , , and , and type I and II DGKs ␣ , ␥ , ␦ , and , respectively ( 18 ). Moreover, the IC 50 values of R59022 and R59949 were ‫ف‬ 25 M and 18 M, respectively ( 18 ).…”
mentioning
confidence: 67%
“…The expression plasmids, p3xFLAG-CMV-pig DGK ␣ ( 19 ), -rat DGK ␤ ( 19 ), -human DGK ␥ ( 19 ), -human DGK ␦ 1-⌬ SAM ( 20,21 ), -human DGK 1 ( 22 ), -human DGK ( 23 ), -human DGK ( 24 ), -human DGK ( 25 ), -human DGK ( 26 ) and -human DGK ( 27 ) were generated as described ( 18 ). cDNAs of DGK ␣ -⌬ 1-196 and DGK ␣ -⌬ 1-332 ( 28 ) were amplifi ed by PCR and inserted into p3x-FLAG-CMV vector.…”
Section: Cdna Constructsmentioning
confidence: 99%
See 3 more Smart Citations